Angele Kremer Marietti (sous la direction de). Auguste Comte. La science, la societe. Paris, França : L’Harmattan, 2009, 219 p. ISBN 978-2-296-08587-9 - Benoit, Lelita Oliveira (Revista Archai, 2010)
.